Compressive strength and porosity tests on bovine hydroxyapatite-gelatin-chitosan scaffolds - Nadia Kartikasari; Anita Yuliati; Indah Liatiana Kriswandini (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Degenerative diseases, aggressive periodontitis, trauma, jaw resection, and congenital abnormalities can cause defects in jaw bone. The surgical procedure for bone reconstruction currently performed is bone regeneration graft (BRG). Unfortunately, this procedure still has many disadvantages. Thus, tissue engineering approach is necessary to be conducted. The main component used in this tissue engineering is scaffolds. Scaffolds used in bone regeneration is expected to have appropriate characteristics with bone, such as high porosity and swelling ratio, low degradation rates, and good mechanical properties. For those reasons, this research used scaffolds made from bovine hydroxyapatite (BHA), gelatin (GEL), and chitosan (K)/BHA-GEL-K as one of biomaterial candidates for bone regeneration. Purpose: This study aimed to determine compressive strength value and porosity size of BHA-GEL-K scaffolds. Method: Compressive strength of BHA-GEL-K scaffolds was tested using autograph with speed 10 mm/ min with a load cell compress machine of 100 kN. Compressive strength was calculated by force divided to surface area. Porosity test was measured using SEM. Scaffold were coated with Pb and Au, then the porosity size is calculated with SEM at 100x magnification. Result: BHA-GEL-K scaffolds had a mean compressive strength value of 174.29 kPa and a porosity size of 31.62 + 147.06 lm. Conclusion: It can be concluded that BHA-GEL-K scaffolds has a good compressive strength, but not yet resemble real bone mass, while porosity of BHA-GEL-K scaffold is appropriate for bone tissue regeneration application.